2016
DOI: 10.20435/1518-70122016108
|View full text |Cite
|
Sign up to set email alerts
|

Cadeias produtivas sustentáveis no desenvolvimento territorial: a castanha na Bolívia e no Acre, Brasil

Abstract: A cadeia produtiva da castanha tem sua produção limitada a dois territórios vizinhos, historicamente baseada na servidão por dívida. Ambas as regiões passaram por profundas modificações nas últimas décadas e oferecem rara oportunidade para comparar as condições de trabalho em uma mesma cadeia produtiva. Apresentamos indicadores de que, ao contrário da Bolívia, a mobilização social no Acre viabilizou a reestruturação da cadeia produtiva, tornando-a mais inclusiva e sustentável.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
0
6
0
4
Order By: Relevance
“…Oliveira and Ipiranga [91] argue that cleaner production in the sector allows for the introduction of social technologies that increase the inclusion of social concerns. Focusing on Brazilian nuts in Amazonia, Brose [98] found that working conditions should be the focus of agri-food because sometimes production develops modern slavery practices, depending on how the social dimension is performed. According to D'Souza and Ikerd [99], all farms have some impact on the environment and the local community where they are sited.…”
Section: Sustainability In the Cashew Supply Chainmentioning
confidence: 99%
“…Oliveira and Ipiranga [91] argue that cleaner production in the sector allows for the introduction of social technologies that increase the inclusion of social concerns. Focusing on Brazilian nuts in Amazonia, Brose [98] found that working conditions should be the focus of agri-food because sometimes production develops modern slavery practices, depending on how the social dimension is performed. According to D'Souza and Ikerd [99], all farms have some impact on the environment and the local community where they are sited.…”
Section: Sustainability In the Cashew Supply Chainmentioning
confidence: 99%
“…For export, the nuts are transported to markets in Belé m and Manaus, from where they are shipped in bulk by sea (Pesce, 2009). The nuts are produced only by extractivism, which favors price fluctuation, being the only product from tree nut sector that is not produced by cultivation (Brose, 2016).…”
Section: Extractive Activitymentioning
confidence: 99%
“…The historical revenue generated by Brazil nut commerce has varied greatly due to influences such as the two World Wars. Currently the annual revenue is about USD 150 million (Brose, 2016;Pesce, 2009).…”
Section: Extractive Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…A frágil organização interna das entidades de representação social dos produtores e comportamentos naturais do ser humano, como o individualismo, foram considerados fatores que dificultavam as ações coletivas em prol da produção e comercialização de castanha articuladas em rede. Muitas são as possibilidades de lidar com essas questões dependendo de cada contexto, mas o que se pode afirmar é que, de modo geral, os problemas mencionados não foram muito diferentes dos que ocorrem nas demais regiões brasileiras produtoras de castanha (GARCÉS et al, 2015;BROSE;2016). Nesse contexto, geralmente é sugerida como solução prioritária a busca pelo estabelecimento de parcerias, a fim de que haja um maior número de pessoas se mobilizando e ajudando na formação e estruturação de um encadeamento de atores e processos.…”
Section: Principais Gargalos Da Cadeia Produtivaunclassified